THE IMPACT OF CONSTITUTIONAL LEGISLATION IN SUPPORTING THE IDEA OF CITIZENSHIP IN THE IRAQI CONSTITUTION - Ajami Turki Jiyad Al-Amiri (Scholar Express Journals, 2022)
Citizenship requires a sense of responsibility in performing duties and claiming rights. This feature is equal between the individual and the state if all the appropriate conditions of freedom, democracy, security, stability, respect for human rights and all the basic criteria that citizenship aims at, and embodying it in all its dimensions on the ground, means building an upscale state with a good society. He lives in security and stability, and therefore the problem of the study revolves around the answer to the main question, which is what is the impact of constitutional legislation in supporting the idea of citizenship in each of the Iraqi constitution? Through the descriptive and analytical research approach, the study came out with a set of results and recommendations, including that the Iraqi constitution emphasizes the need to ensure the right to participation and equality, in a way that supports the idea of citizenship. The guarantor of the right to participation and equality in a way that supports the idea of citizenship in Iraq is the constitution and judicial oversight, so we recommend the need to put in place legal and oversight mechanisms to activate the principle of the supremacy of the constitution as a basic guarantee for democracy and support for the idea of citizenship, and to protect the rights and freedoms of individuals, and to guarantee the principle of legitimacy with its provisions, and then preserve the principle of legitimacy It is sponsored by the constitutional courts and councils. Otherwise, the principle of the supremacy of the constitution becomes a slogan without content and a word without content
Keywords: Legislation; constitution; citizenship; participation